Development of a caregiver-reported measure to support systematic assessment of people with dementia in long-term care: The Integrated Palliative care Outcome Scale for Dementia. (July 2017) - Ellis-Smith, Clare; Evans, Catherine J; Murtagh, Fliss EM; Henson, Lesley A; Firth, Alice M; Higginson, Irene J; Daveson, Barbara A
Background: Symptom burden is common for long-term care residents with dementia which if untreated compromises quality of life. Measurement tools can support assessment of symptoms and problems but are not widely used in long-term care settings. We developed the Integrated Palliative care Outcome Scale for Dementia derived from the Palliative care Outcome Scale, Palliative care Outcome Scale–Symptom and Integrated Palliative care Outcome Scale. Aim: To examine the content validity, acceptability and comprehension of Integrated Palliative care Outcome Scale for Dementia for routine use in long-term care settings for people with dementia and to refine Integrated Palliative care Outcome Scale for Dementia. Design: A multi-method qualitative study consisting of focus groups, semi-structured interviews and cognitive interviews. Setting/participants: Three residential long-term care settings in London, UK. Focus group and semi-structured interview participants included caregiver staff, family, general practitioners and district nurses. Caregiver staff were sampled purposively for cognitive interviews. Results: A total of 26 respondents participated in the focus groups ( n  = 21) or semi-structured interviews ( n  = 5) and 10 caregiver staff completed cognitive interviews. Additional symptoms and problems included agitation, wandering, sleep problems, communication problems and diarrhoea. Refinements or lay terms were required to improve comprehension and consistency of item response for nausea, drowsiness, delusions/hallucinations, agitation, loss of interest, communication problems and interaction. A video presentation was required to support comprehension of instructions and assessment of verbally compromised residents. Conclusion: Integrated Palliative care Outcome Scale for Dementia is a comprehensive and acceptable caregiver-reported measure to detect symptoms and problems in dementia. It is suitable for caregiver staff without professional training as it has been refined and tailored to maximise caregiver expertise, ready for further psychometric testing.